Towards sustainable food crop production: Drivers of shift from crop production to mining activities in Ghana's arable lands - Wongnaa, Camillus Abawiera; Nti, Emmanuel Kwame; Acheampong, Patricia Pinamang; Bannor, Richard Kwasi; Prah, Stephen; Babu, Suresh Chandra (Elsevier, 2024)
This study contributes to the observed reduction of arable lands discourse by examining the shift in land use patterns as well as factors influencing farmers' shift from crop production to mining activities. To achieve this, we employed a combination of Geographic Information System (GIS) technology and Cragg's Double Hurdle Econometric Model as analytical tools. Our approach integrates an econometric model of land use with GIS simulations that predict the spatial pattern of land-use change. The results revealed that crop production lands have been converted into artisanal small-scale mining (galamsey) sites, a development which has implications on food security, life on land and effective utilizations of land and water resources. The results also showed that membership in Farmer-Based Organizations (FBOs), access to credit, and low yield of food crops influenced farmers to shift from crop production to participate in mining activities. In addition, the extent of participation in mining was influenced by family size, membership in FBOs, and low crop yield. While mining operations offer substantial economic benefits, it is crucial to strike a balance between land use for mining activities and food crop production. This is because it has the potential to worsen recent hikes in food prices and subsequently leading to rising inflation rates in Ghana. Our findings have implications on achieving multiple SDGs, viz. SDG 2 (Zero Hunger), SDG 6 (Clean Water and Sanitation) and SDG 15 (Life on Land) as minimizing illegal mining helps increase food production as well as protect water bodies and land. We therefore suggest that government should take steps to make credit accessible to farmers by collaborating with financial institutions and also collaborate with Crops Research Institutes to develop high-yielding crop varieties. Future research could focus on exploring the impact of participating in mining activities on the profitability of food crop production in Ghana.